Peran Aktif Guru Geografi Menanamkan Kesadaran Cinta Lingkungan Pada Siswa Tingkat SMA di Kota Ternate - Jainudin Hasim; Yuni Andriyani Safitri; Fitriana Ibrahim; Asnita Ode Samili (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is a qualitative descriptive study that uses secondary data as the main data. Data were collected through literature studies from the results of previous research in high schools throughout Ternate City. The population of this research is Geography teachers of high school in Ternae City. The population of Geography teachers is 20 Geography teachers. By using a total sampling technique. The sample of geography teachers is 20 teachers. The student population is 890 students. Instruments of data collection using questionnaires, interviews and documentation. The data that had been collected were analyzed using descriptive percentages. The results showed that the geography teachers in instilling awareness of students' love for the environment were in the good category. The teacher's role in fostering the character of students in Ternate City High School has done its role very well, namely by educating, guiding and directing students to always care about the school environment, every day on the sidelines of learning geography teachers provide education about environmental love through learning videos and its application in daily life by teaching students to dispose of garbage in its place and cleaning the school environment.